Integrating Physical, Mental, and Emotional Wellbeing into HR Practices - Maluegha, Merliana Inna; Ibrahim, Muhdi B. Hi; Irawan, Andri; Yendra, Yendra; Lina, Ros (Advances: Jurnal Ekonomi & Bisnis, 2024)
The aim of this qualitative literature review is to investigate the integration of physical, mental, and emotional well-being into HR practices. The research design involves a systematic approach to selecting, analyzing, and synthesizing literature on the topic. Comprehensive searches of academic databases, journals, books, and other scholarly sources were conducted to identify key themes, concepts, and theories relevant to the research question. Data collection involved gathering and critically appraising various sources, including empirical studies, theoretical frameworks, and qualitative analyses. Qualitative data analysis techniques such as thematic analysis and content analysis were employed to identify recurring themes, patterns, and trends across the literature. The findings reveal several key insights into the benefits, challenges, and strategies associated with integrating well-being into HR practices. Prioritizing employee well-being offers benefits such as reduced absenteeism, enhanced productivity, and improved job satisfaction. However, challenges such as lack of organizational commitment, cultural stigma, and resistance to change hinder effective implementation. Overall, the study underscores the importance of adopting a holistic approach to well-being management and fostering collaboration both within and outside the organization.